2011
DOI: 10.1074/jbc.m110.153221
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-induced Enhancement of c-Myc Translation in Multiple Myeloma Cells

Abstract: Prior work indicates that IL-6 can stimulate c-Myc expression in multiple myeloma (MM) cells, which is independent of effects on transcription and due to enhanced translation mediated by an internal ribosome entry site in the 5-UTR of the c-Myc RNA. The RNA-binding protein hnRNP A1 (A1) was also critical to IL-6-stimulated translation. Because A1 shuttles between nucleus and cytoplasm, we investigated whether the ability of IL-6 to enhance Myc translation was mediated by stimulation of A1 shuttling. In MM cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“… 3 In this regard, we found that exogenous interleukin-6 (IL-6) or insulin-like growth-factor-1 (IGF-1) or hepatocyte growth-factor (HGF) significantly reduced miR-125b-5p expression in all MM cell lines except U266 cells ( Figure 6a ), which express L-Myc instead of c-Myc. Since c-Myc suppresses miR-125b transcription 39 , 40 and is upregulated by IL-6, IGF-1 and HGF, 40 , 41 , 42 we investigated whether these factors downregulate miR-125b in MM cells through c-Myc induction. Specifically, we treated c-Myc-expressing SK-MM-1 and c-Myc-defective U266 cells with the 10058-F4 small molecule inhibitor of Myc–Max heterodimerization 38 and with the JQ1 BET-bromodomain inhibitor, which is reported to inhibit c-Myc transcription.…”
Section: Resultsmentioning
confidence: 99%
“… 3 In this regard, we found that exogenous interleukin-6 (IL-6) or insulin-like growth-factor-1 (IGF-1) or hepatocyte growth-factor (HGF) significantly reduced miR-125b-5p expression in all MM cell lines except U266 cells ( Figure 6a ), which express L-Myc instead of c-Myc. Since c-Myc suppresses miR-125b transcription 39 , 40 and is upregulated by IL-6, IGF-1 and HGF, 40 , 41 , 42 we investigated whether these factors downregulate miR-125b in MM cells through c-Myc induction. Specifically, we treated c-Myc-expressing SK-MM-1 and c-Myc-defective U266 cells with the 10058-F4 small molecule inhibitor of Myc–Max heterodimerization 38 and with the JQ1 BET-bromodomain inhibitor, which is reported to inhibit c-Myc transcription.…”
Section: Resultsmentioning
confidence: 99%
“…25 Furthermore, interleukin-6, a critical cytokine for myeloma growth, also stimulates c-MYC translation. 26 In this work, we describe a novel mechanism to control the expression of c-MYC: the regulation of its translation by the HMT MMSET.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 can enhance the translation of c-Myc in multiple myeloma cells [ 42 ]. Moreover, IL-6 can promote c-Myc expression and cultured vascular smooth muscle cell proliferation [ 43 ].…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…STAT3 activation transduces IL-6 signaling, which induces the production of acute phase proteins such as fibrinogen and haptoglobin. IL-6 could enhance c-Myc protein expression in multiple myeloma cells independent of any effect on Myc transcription [ 42 ]. Also, IL-6 can reverse CD33 expression by upregulating Myc and subsequently downregulating CCAAT/enhancer binding protein (CEBPA) expression in myeloma cells [ 43 ].…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%